DINAMIKA PROBLEMATIKA SOSIAL PERLINDUNGAN BURUH MIGRAN INDONESIA PASCA REFORMASI DAN RELEVANSINYA DENGAN TANTANGAN WIRAUSAHA DI ERA MASYARAKAT EKONOMI ASEAN (MEA) - Raden Muhammad Mihradi; Ferry Muhammadsyah Siregar (Jurnal Kawistara, 2017)
The problems of Indonesian migrant workers (TKI), especially Indonesian migrant workers are complex. Weak regulation in favor of migrant workers and regulatory abuses are common. In addition, there is no clarity as to what can be done for ex-migrant workers working abroad. There is an idea in the era of the ASEAN Economic Community (MEA) that former migrant workers be transformed into entrepreneurs with competency and integrity that conform to international standards. This paper will answer deeper regarding the dynamics and social problems among migrant workers and the potential for transformation into entrepreneurs in the era of the MEA. The methods were used in this study are qualitative methods as well as social and legal (juridical) perspectives related to regulation by conducting library research and collecting relevant documents.